The Interrelation Between Textile Engineering Graduates’ Results And Their Job Performance In Textile Industry Of Bangladesh - Haque, Mahbubul; Chowdhury, Tanvir Ahmed; Rahman, Mominur; Smrity, Shamima Akter; Islam, Azharul; Mahbub, Tariq (European Scientific Journal, ESJ, 2021)
It has been a long that educators, employers, and researchers are trying to relate the university grades and job performance of graduates to improve the quality of teaching and make recruitment easy. However, a concrete conclusion is yet to achieve. In the current study, attempts were made to correlate the relationship between the grades obtained by the textile graduates of a university and their performance in the textile industries in Bangladesh using the Likert scale. Twenty dimensions of quality were identified and corresponding graduatesâ€™ competence in these dimensions were evaluated and a relation was made with the grades obtained by the graduates. It was found that students with excellent academic results showed their excellence in the majority of the dimensions of quality over the students with average and poor results. Students with average and poor results also showed their excellence for few quality dimensions and no relation could be proposed. From this study, the authors concluded that, in general, the graduates’ job performance was highly related to the GPA obtained by the graduates of that university.